Employee Engagement in Nepalese Commercial Banks: A Focused Group Discussion Analysis - Kharel, Shreekrishna; Niraula, Ganesh Prasad; Mainali, Bhawani Prasad (Tribhuvan University Journal, 2024)
Many organizations around the world have been dealing with issues related to employee altruism, fatigue, and burnout in the twenty-first century. In order to address the issues, all organizations strive to increase the cognitive, physical, and emotional engagement of their workforce. So, this study aims to investigate the Employee Engagement in Nepali Commercial Banks: A Focused Group Discussion Analysis in order to address this issue. This research is descriptive and based on the previous research findings applying the Focused Group Discussion technique of sampling under qualitative research assumption. The employees’ engagement domains vigor, dedication and absorption have been found positive. Similarly, the availability, safety and meaningfulness all had positive impact on employees’ engagement in the Nepali commercial banks. This study is primarily based on qualitative analysis by taking the views of employees using FGD of the participants of commercial banks in the three districts of Kathmandu Valley. Researchers and company executives looking to learn more about the types and level of engagement activities going on in Nepali commercial banks find this study 64 to be useful. This research may be the first of its kind in the context of Nepali commercial bank.